Pengaruh Pembiasan Keagamaan terhadap Karakter Disiplin Siswa di Sekolah Menengah Pertama Muhammadiyah 9 Kota Bandung - Sitti Chadidjah; Ela Jauhar Kamilah; Fitria Nurlaeliah; Sheila Luthfiah; Fadhillah Azzahra; Siti Sarah Nurfitriyani; Muhammad Nur Soleh (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Agama Islam Nahdlatul Wathan Samawa Sumbawa Besar, 2026)
The development of students' disciplinary character is one of the educational goals, especially in addressing behavioral issues in the school environment. Consistent and continuous religious habituation becomes one of the efforts made by schools in dealing with these issues. This study aims to determine and analyze the influence of religious habituation on the disciplinary character of students at SMP Muhammadiyah 9 Kota Bandung. This study uses a descriptive method with a quantitative approach, where the research data analysis is carried out using descriptive statistical analysis and inferential analysis with simple linear regression through validity and reliability tests of the data collected via a Likert scale questionnaire instrument. The hypothesis testing is done using a t-test at a significance level of 0.05. Research results show that religious habituation has a positive and significant influence on students' discipline character. This can prove that the better the religious habituation activities conducted at school, the higher the level of discipline character possessed by students.